Training Needs of Jordanian EFL Teachers in Pronunciation Instruction: A Case Study - Elkouz, Ahlam; Muñoz-Luna, Rosa María (University of Jordan, 2023)
Objectives: This study aims to enhance our understanding of the training requirements of Jordanian EFL teachers regarding English pronunciation and speaking instruction, considering the perspectives of both teachers and supervisors. Methods: The study involved the participation of 372 teachers and 6 supervisors. The teachers completed a questionnaire expressing their opinions on their needs for capacity building in English pronunciation instruction, while supervisors engaged in semi-structured interviews to discuss their perspectives on teacher training in this area.Both qualitative and quantitative data were analyzed. Results: The study revealed that 74.8% of the participating teachers expressed a need for more specialized training in teaching English pronunciation. This need was further emphasized by the supervisors during the interviews. Conclusions: Jordanian EFL teachers require tailored capacity building in the instruction of English pronunciation and speaking. The findings from this research can be utilized by supervisors to emphasize the necessity for remedial programs for both teachers and students. Additionally, supervisors can propose a plan for training teachers on the use of new technologies that facilitate the teaching of this skill.
Keywords: Lengua inglesa - Estudio y enseñanza - Extranjeros; Lengua inglesa - Pronunciación; Profesores - Formación profesional; Training needs; Pronunciation instruction; EFL teachers